Kadar Alkohol, Kadar Gula, Dan Derajat Keasaman Pada Fermentasi Minuman Kombucha Salak Bali - Dwi Ariesta Wijaya Putra, Anak Agung Ngurah; Ary Widnyani, Ida Ayu Putu; Elza Fitriani, Pande P. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
Indonesia as a tropical country has various types of fruit. One of the famous fruits in Indonesia is salak. Salak bali (Salacca zalacca Var. ambonensi) is one of the local varieties of salak Bali. Salak bali contains protein, carbohydrates, fat, calcium, phosphorus, iron and vitamin C. In addition, salak contains sucrose, fructose, and glucose. The sugar contained in the salak will be used for fermentation to produce new products that will increase the selling value of the salak. One of the products that can be made from salak fruit is kombucha salak drink. Kombucha is a fermented drink that has a sour and slightly sweet taste and contains alcohol. The purpose of this study was to determine the degree of acidity, alcohol content, and sugar content of the fermented kombucha salak drink. This study uses variations in fermentation time. The results showed that the longer the fermentation time, the more alcohol produced, but the lower the sugar content. In addition, the longer the fermentation also causes the resulting product to be more acidic.